Pajak Menurut Syari’ah - Arifin, Gusfahmi (Sahabat Publikasi, 2024)
This study aims to find out how the position of tax law according to the view of Islamic law. This is very important to do because 82% of the source of state revenue of the Republic of Indonesia comes from taxes. In conditions of such high dependence on taxes, in the midst of society there are still pros and cons about the existence of tax law. This research is focused on seeing how the practice of collecting Income Tax (PPh), Value Added Tax (VAT) and Land and Building Tax (PBB) as the three largest sources of state revenue in Indonesia, then comparing it with the practice of collecting state revenue during the reign of the Prophet SAW, analyzing the causes of the emergence of taxes in Islamic governments, formulating tax criteria according to sharia and implementing taxes according to shari'a in collection PPh, VAT, and UN in Indonesia. This study uses a conventional research model that uses a qualitative approach and data collection methods based on documents and literature. The results showed that taxes have existed since the reign of the Prophet (peace be upon him) in the form of Jizya, Kharaj, 'Usyr, in addition to the main sources of income of Ghanimah, Fa'i and Zakat. Of the 6 types of income sources above, currently only Zakat can be collected, resulting in the emergence of Ijtihad in the form of Tax (Dharibah) by Ulil Amri to overcome the lack / vacancy of Baitul Mal. Although Ulama allows taxes (Dharibah), but in collecting income tax, VAT and UN in Indonesia it is still not in accordance with Shari'ah, so there are taxes that need to be improved and some types of taxes must be removed.